The Application of Portfolios to Assess Progress in Writing of EFL Students at Secondary Schools in Banda Aceh - Eridafithri Eridafithri (Studies in English Language and Education, 2015)
Portfolios are one of the alternatives that can be used for writing assessment. Portfolios are not common in the curriculum. The lack of dissemination to language teachers have made portfolios disregarded. In order to encourage teachers to use portfolios for assessment of writing, they need to have adequate information about portfolios, how they can be used for assessment as well as the benefits of using them for assessment. This study discusses why teachers do not use portfolios for assessing writing done by senior high school students. It focuses on English teachers at Islamic senior high schools in Banda Aceh and Aceh Besar, and also looks at alternatives to help teachers use portfolios for assessment. The 26 teachers who participated in this study were given a questionnaire in order to find out their background knowledge related to portfolios and the difficulties they faced as teachers. Data from the questionnaire was supported by observations made by the researcher whilst monitoring their teaching. The results of this study showed that a large percentage of teachers found it difficult to design a rubric/set of instructions for using portfolios for writing assessment, whilst from the observation it was revealed that the complexities of correcting portfolios discouraged them from using portfolios as one of their means of assessment.